1999
DOI: 10.1017/cbo9780511613470
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Transfer in the Atmosphere and Ocean

Abstract: This text provides a foundation in both the theoretical and practical aspects of radiative transfer, for advanced students of atmospheric, oceanic and environmental sciences. The transfer of solar and infrared radiation through optically-thick clouds, aerosol layer, and the oceanic mixed layer is presented through the use of heuristic models of scattering and absorption, and a systematic approach to formulation and solution of the radiative transfer equation. Problems such as the transmission of ultraviolet ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
369
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(378 citation statements)
references
References 0 publications
7
369
0
2
Order By: Relevance
“…As a variant of the two-stream solution, the delta-Eddington method might appear crude in comparison to the many other solvers available (e.g. Thomas and Stamnes, 1999). Indeed four-stream rather than two-stream solvers have been recommended for improved accuracy in scattering calculations in the Community Radiative Transfer Model (Bennartz and Greenwald, 2011).…”
Section: Sensitivity To Assumptions and Inaccuracies In Radiative Tramentioning
confidence: 99%
“…As a variant of the two-stream solution, the delta-Eddington method might appear crude in comparison to the many other solvers available (e.g. Thomas and Stamnes, 1999). Indeed four-stream rather than two-stream solvers have been recommended for improved accuracy in scattering calculations in the Community Radiative Transfer Model (Bennartz and Greenwald, 2011).…”
Section: Sensitivity To Assumptions and Inaccuracies In Radiative Tramentioning
confidence: 99%
“…The exact phase function in biological tissue is still a research issue [34]. In the past, the Henyey-Greenstein phase function (HGPF) was widely used for modeling radiative transfer in many applications [34], [35]. However, due to some discrepancies, recently, researchers have combined a highly anisotropic phase function [(e.g., the Henyey-Greenstein phase function)], and a low anisotropic phase function [e.g., the Rayleigh phase funcition (RLPF)] [36] to approximate the phase function in biological tissue [36].…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…(2) and N in Eq. (3) seem to be independent, it was shown that N = K/2 gives numerically stable results (Thomas and Stamnes, 1999). Thus N = K/2 is assumed in Section 2.…”
Section: Definition Of the Problemmentioning
confidence: 98%
“…Each ordinate corresponds to one equation, and there are N ordinates per hemisphere. The azimuthal dependence of radiance is expressed via Fourier series with M harmonics, where the system of N linear equations is solved independently for each m = 0…M (Thomas and Stamnes, 1999) providing solution in i = 1…N discrete points 1 1 ; 0 , 1 i i P P z r .…”
Section: Introductionmentioning
confidence: 99%